A Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic and its preparation method and application

By introducing TiO2nws and BaSrAlSiO into Yb2Si2O7 ceramics, the Yb2Si2O7-BaSrAlSiO/TiO2nws composite ceramics are formed, which solves the problems of low electromagnetic wave absorption strength and narrow effective absorption band in harsh environments of absorbing materials, and achieves efficient electromagnetic wave absorption and improvement of anti-oxidation properties.

CN119143490BActive Publication Date: 2025-04-18STATE OWNED SIDA MASCH MFG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411078703.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2025-04-18
Estimated Expiration
2044-08-07

AI Technical Summary

Technical Problem

In harsh environments, existing absorbing materials have low electromagnetic wave absorption strength, narrow effective absorption frequency band, and insufficient oxidation resistance, making it difficult to meet the high-demand application needs.

Method used

By introducing TiO2nws and BaSrAlSiO on the basis of Yb2Si2O7 ceramics, the Yb2Si2O7-BaSrAlSiO/TiO2nws composite ceramics are formed to optimize the dielectric properties and electromagnetic wave absorption characteristics of the material.

Benefits of technology

It significantly improves the electromagnetic wave absorption and oxidation resistance of the material, expands the effective absorption bandwidth, can absorb 99.99% of the electromagnetic waves, and maintains excellent performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143490B_ABST
    Figure CN119143490B_ABST
Patent Text Reader

Abstract

The present invention provides a Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic and its preparation method and application, which solve the problems existing in existing microwave absorbing ceramics. The present invention adopts the research and development path of introducing TiO2nws and BaSrAlSiO on the basis of Yb2Si2O7 ceramics, and adopts a cold pressing method to prepare a ternary ceramic Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic with different energy gaps and structural properties, which can achieve adjustable dielectric constant and electromagnetic wave absorption characteristics by changing the mass ratio of raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microwave absorbing materials, and specifically relates to a Yb2Si2O7-BaSrAlSiO2 / TiO2nws composite ceramic and a preparation method and application thereof. Background Art

[0002] At present, the rapid development of wireless communications and the increasing popularity of smart homes, transportation and medical equipment have brought convenience to the fast-paced society. At the same time, the application of a large number of electronic devices has also greatly increased electromagnetic radiation, causing serious electromagnetic pollution problems. These electromagnetic pollutions not only interfere with the operation of electrical equipment, but are also harmful to human health and the natural environment, and even affect safety or cause major accidents. For this reason, it is of great significance to develop high-performance electromagnetic wave absorbing materials that convert incident electromagnetic waves into heat or dissipate them through the interface. Moreover, with the widespread application of absorbing materials in certain equipment, higher requirements are put forward for the strong absorption of electromagnetic waves in terms of anti-oxidation.

[0003] Rare earth silicates have low thermal expansion coefficients, good chemical stability and corrosion resistance, and are the most promising environmental barrier coating materials for high-temperature silicon-based ceramics. Among them, Yb2Si2O7 is a typical high-temperature structural ceramic, widely used in high-temperature oxidation-resistant coatings, corrosion-resistant ceramics and heat-resistant shock coatings, and has strong environmental adaptability, but it also has the disadvantages of low absorption intensity and low effective absorption band. From an application point of view, it cannot be used as an absorption material. In addition, research on absorption materials is still mainly focused on traditional absorption materials, with little success.

[0004] In view of the current situation, the research team of this invention believes that it is necessary to change conventional thinking and not be limited by the research and development path of traditional absorbing materials. They develop a new type of microwave absorbing material that can be used in harsh environments to meet the high requirements of harsh environments on the absorbing performance and antioxidant properties of absorbing materials. Summary of the invention

[0005] Aiming at the high requirements on the performance of absorption materials in harsh environments and the bottleneck period of the current research and development of traditional absorption materials, the present invention provides a Yb2Si2O7-BaSrAlSiO2 / TiO2nws composite ceramic and a preparation method and application thereof.

[0006] The concept of the present invention:

[0007] The research team of the present invention believes that Yb2Si2O7 has strong environmental adaptability and is very suitable for harsh environments. However, due to its low absorption intensity and low effective absorption band, there has always been a prejudice that it cannot be used as an absorption material. The research team of the present invention has taken a different approach and further developed Yb2Si2O7 ceramics in order to obtain an absorbing material that meets the requirements.

[0008] First, the present invention has conducted an in-depth analysis of the problems existing in Yb2Si2O7 ceramics, and found that it is mainly because this type of ceramic matrix has a relatively high real part of the dielectric constant, a large amount of electromagnetic waves will be reflected on the surface of the material, and the electromagnetic waves cannot enter the material as much as possible to be absorbed. At the same time, due to the lack of an effective electromagnetic wave dissipation phase, its electromagnetic wave loss capacity is insufficient. In view of this factor, and the fact that traditional electromagnetic wave absorbing ceramics are composed of absorbents and carriers, it is proposed to first introduce absorbents to overcome the problems currently faced by this type of ceramic matrix. TiO2nws, as a conductive semiconductor with excellent performance, was selected by the research team of the present invention as an absorbent. Thus, the present invention prepares a composite ceramic Yb2Si2O7 / TiO2nws with certain electromagnetic wave absorption capacity and chemical stability by adjusting the ratio and process flow. This is a breakthrough. The unpopular Yb2Si2O7 is optimized to be used as a microwave absorption material. However, it is not enough to stop there. Although Yb2Si2O7 / TiO2nws ceramics can be used as absorption materials in harsh environments and can meet the requirements of wave absorption performance, corrosion resistance and oxidation resistance, it is found through research that Yb2Si2O7 / TiO2nws ceramics have poor electromagnetic wave absorption capacity. The effective absorption bandwidth (EAB) range is still small, and the broadband absorption capability is relatively limited. In the face of increasingly high requirements, there is still room for improvement. For this reason, it is planned to further introduce BaSrAlSiO2, which can polymerize with TiO2nws to form small particles, increase the internal defects of the ceramics, thereby increasing the polarization effect, and forming a small-area thin film on the surface of the ceramics, enhancing the absorption of electromagnetic waves and increasing the response to electromagnetic waves of specific wavelengths, thereby further improving the requirements for broadband absorption performance. As a high-temperature oxidation-resistant coating, corrosion-resistant ceramic and heat-shock-resistant coating, it has strong environmental adaptability.

[0009] To achieve the above purpose, the technical solution provided by the present invention is:

[0010] A method for preparing Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics, characterized in that:

[0011] Yb2Si2O7 powder, BaSrAlSiO powder and TiO2 powder were uniformly mixed in a mass ratio of 10:1-3:1, and then cold pressed at a pressure of 15-25 MPa to form a cold pressed shape (35×15×4 mm 3 The resultant Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics were obtained by sintering the resulting ceramics in an air atmosphere at a temperature of 1100-1500°C for 1.5-2.5 h.

[0012] Furthermore, Yb2Si2O7 powder is prepared by a sol-gel method, and the preparation method of the Yb2Si2O7 powder is as follows:

[0013] Dissolve Yb(NO3)3·6H2O in deionized water to obtain solution A;

[0014] Dissolve ethyl orthosilicate in ethanol and stir to obtain solution B;

[0015] At room temperature, solution A and solution B are mixed and stirred to obtain a transparent gel C;

[0016] After the gel C is dried, it is calcined to obtain powder D; wherein the drying process conditions are: first drying at 70-90°C for 20-30h, and then drying at 110-150°C for 11-13h; the calcination process conditions are: calcination temperature is 1100-1200°C, and calcination time is 2-3h;

[0017] The powder D was ball-milled for 20-60 min. This process was repeated 5-15 times with a time interval of 10-20 min between two adjacent millings. Yb2Si2O7 powder was obtained after drying.

[0018] Furthermore, BaSrAlSiO powder is prepared by a sol-gel method, and the preparation method of the BaSrAlSiO powder is as follows:

[0019] BaCO3, Al(NO3)3·9H2O and Sr(NO3)2 were dissolved in citric acid to obtain solution E;

[0020] Dissolve ethyl orthosilicate in ethanol and stir to obtain solution F;

[0021] At room temperature, solution E and solution F were mixed and stirred to obtain a transparent gel G;

[0022] After the gel G is dried, powder H is obtained; wherein the drying process conditions are: first drying at 70-90°C for 20-30h, and then drying at 110-150°C for 11-13h;

[0023] The powder H was ball-milled for 20-60 min. The process was repeated 5-15 times with a time interval of 10-20 min between two adjacent millings. BaSrAlSiO powder was obtained after drying.

[0024] The ball milling process is used to grind the small particles in powder D and powder H into powder, which is beneficial to the subsequent tableting process because the small particles cannot be pressed into shape.

[0025] Furthermore, TiO2nws powder is prepared by a hydrothermal method, and the preparation method of the TiO2nws powder is as follows:

[0026] Tetrabutyl titanate, isopropanol and a NaOH solution with a molar concentration of 0.08-0.12 mol / L were mixed in a volume ratio of 1:2:2 to obtain a solution I, and the solution was stirred for 20-60 min and then transferred to a reactor for a hydrothermal reaction at 170-190° C. for 11-13 h;

[0027] After natural cooling, the reaction precipitate was washed with deionized water, and then washed with a 0.05-0.15 mol / L HCl solution until the pH value was 6.5-7.5, and then filtered, and the filter cake was dried at 70-90 ° C to obtain powder J;

[0028] Powder J was calcined at 700-900 °C in air for 1.5-2.5 h to obtain TiO2nws powder.

[0029] Further, the molar ratio of Yb(NO3)3·6H2O, ethyl orthosilicate, ethanol and deionized water is 1:1.2:4:4;

[0030] The drying process conditions of gel C were: first drying at 80°C for 24 h, then drying at 110°C for 12 h; the calcination process conditions were: heat treatment at 1100°C for 2 h;

[0031] Powder D was ball-milled for 30 min using a planetary ball mill. This process was repeated 10 times with a time interval of 15 min between each milling.

[0032] Further, the molar ratio of BaCO3, Al(NO3)3·9H2O, Sr(NO3)2, tetraethyl orthosilicate, ethanol and citric acid is 1:2:1:1.2:3:3;

[0033] The process conditions for drying gel G were: first drying at 80°C for 24 h and then drying at 120°C for 12 h;

[0034] The powder H was ball-milled for 30 min using a planetary ball mill. This process was repeated 10 times with a time interval of 15 min between each milling.

[0035] Furthermore, the molar concentration of the NaOH solution was 0.1 mol / L; the solution I was stirred for 30 min, and the temperature of the hydrothermal reaction was 180 °C and the time was 12 h;

[0036] The mixture was washed with 0.1 mol / L HCl solution until the pH value was 7, and then filtered. The filter cake was dried at 80° C. to obtain powder J.

[0037] Powder J was calcined at 800 °C in air for 2 h to obtain TiO2nws powder.

[0038] Preferably, Yb2Si2O7 powder, BaSrAlSiO powder and TiO2nws powder are uniformly mixed in a mass ratio of 10:3:1, and then cold pressed at a pressure of 20 MPa. After pressing and molding, they are placed in an air atmosphere at a temperature of 1300°C and sintered for 2 hours to obtain Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics.

[0039] The present invention also provides a method for preparing Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics, which is special in that the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics are prepared by the above-mentioned preparation method. The dielectric properties of the composite ceramic matrix can be adjusted by changing the content of BaSrAlSiO powder, so that the composite ceramics have the ability to absorb electromagnetic waves.

[0040] In addition, the present invention also provides the application of the above-mentioned Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic in microwave absorption.

[0041] And, an extension of the application, a wave absorbing material, the active ingredient of which is the above-mentioned Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic.

[0042] Principle of the present invention:

[0043] The present invention adopts a research and development path based on Yb2Si2O7 ceramics by introducing TiO2nws and BaSrAlSiO, and adopts a cold pressing method to prepare a ternary ceramic, Yb2Si2O7-BaSrAlSiO / TiO2nws ceramic, which can achieve adjustable dielectric constant and electromagnetic wave absorption characteristics by changing the mass ratio of raw materials, and has different energy gaps and structural properties. The present invention constructs three heterostructures, namely Yb2Si2O7, TiO2nws, and BaSrAlSiO. These three structures can effectively reduce the energy gap of the ceramic heterojunction, achieve higher electron mobility when the conductive phase content is low, and improve the conductive loss of the material. BaSrAlSiO can enhance the polarization ability of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics and adjust the dielectric constant of the material, so that electromagnetic waves enter the material instead of reflecting on the surface of the material. Electromagnetic waves are constantly reflected and scattered between Yb2Si2O7, TiO2nws and BaSrAlSiO, thereby increasing the transmission path of electromagnetic waves and achieving effective loss. The internal heterogeneous interface and defects of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics act as polarization centers, which improve the loss capacity of ceramic heterojunctions to electromagnetic waves and the frequency range of electromagnetic wave absorption bandwidth.

[0044] The advantages of the present invention are:

[0045] 1. The present invention introduces BaSrAlSiO into the material based on Yb2Si2O7-TiO2nws ceramics to form Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics. The composite ceramics have improved the electromagnetic wave absorption performance of the original Yb2Si2O7-TiO2nws ceramics. The heterogeneous structure formed inside the material has an important influence on the dielectric properties of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics; at the same time, the structural characteristics of the ceramics are controlled by adjusting the content ratio (mainly referring to the content of BaSrAlSiO powder). With the increase of BaSrAlSiO powder content, the electromagnetic wave dissipation performance of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics is significantly improved. When the ratio of Yb2Si2O7 powder, BaSrAlSiO powder and TiO2nws powder is 10∶3∶1, Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics can absorb 99.99% of electromagnetic waves, RL min It can reach -35 dB, and the EAB reaches 4.1 GHz (7.8 GHz-8.0 GHz and 12.0 GHz-15.5 GHz), which increases the frequency range by 56% compared with the effective absorption bandwidth (EAB) of Yb2Si2O7-TiO2nws ceramics.

[0046] 2. The process flow of the method of the present invention is extremely simple, easy to operate and implement, and suitable for large-scale industrial production and application.

[0047] 3. The electromagnetic wave absorption performance of the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic of the present invention is controllably adjustable (i.e., the structural characteristics of the ceramic are controlled by adjusting the content ratio). The overall advantage is due to the excellent dielectric properties of the heterojunction formed when BaSrAlSiO is introduced into the Yb2Si2O7-TiO2nws ceramic. The performance of the heterojunction of the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic does not decrease over time under high temperature, water and oxygen environments, and has the advantages of strong environmental adaptability, etc., and has outstanding application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 SEM images of Yb2Si2O7-TiO2nws ceramics and microwave absorbing composite ceramics with different BaSrAlSiO contents (Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics), (a) is the SEM image of Yb2Si2O7-TiO2nws ceramics, (b)-(d) are the SEM images of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics with different BaSrAlSiO contents;

[0049] Figure 2 XRD patterns of Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics with different BaSrAlSiO contents;

[0050] Figure 3 TEM images of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics with a mass ratio of Yb2Si2O7, BaSrAlSiO and TiO2nws of 10:3:1, (a) morphology at low magnification; (b)-(d) TEM images at high resolution.

[0051] Figure 4Three-dimensional RL curves and two-dimensional RL curves of Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics, (a)-(b) three-dimensional RL curves and two-dimensional RL curves of the composite ceramics when the mass ratio of Yb2Si2O7, BaSrAlSiO and TiO2nws powders is 10∶1∶1; (c)-(d) three-dimensional RL curves and two-dimensional RL curves of the composite ceramics when the mass ratio of Yb2Si2O7, BaSrAlSiO and TiO2nws powders is 10∶2∶1; (e)-(f) three-dimensional RL curves and two-dimensional RL curves of the composite ceramics when the mass ratio of Yb2Si2O7, BaSrAlSiO and TiO2nws powders is 10∶3∶1. DETAILED DESCRIPTION

[0052] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:

[0053] According to the research and development path, before the introduction of BaSrAlSiO, Yb2Si2O7 / TiO2 ceramics were first developed. The preparation method of the ceramics is as follows: Yb2Si2O7 powder and TiO2nws powder are uniformly mixed in a mass ratio of 20:1-3, and then cold pressed at a pressure of 15-25 MPa. After pressing and molding, they are placed in an air atmosphere at a temperature of 1100~1500°C and sintered for 1.5-2.5h to obtain Yb2Si2O7 / TiO2 ceramics. This is the first generation product. In the process of studying this material, the optimal mass ratio of Yb2Si2O7 powder to TiO2nws powder was screened out to be 10:1. The ceramics prepared under this ratio can be used as microwave absorbing materials, and its RL min It can reach -45dB, and the EAB is 2.3GHz (10.1GHz-12.4GHz). In order to further improve its broadband absorption, the present invention introduces BaSrAlSiO on the basis of this ratio, and screens the optimal ratio through the following examples to obtain a composite ceramic with good performance and a wider frequency absorption range.

[0054] Example 1

[0055] A method for preparing Yb2Si2O7-BaSrAlSiO2 / TiO2nws composite ceramics, the specific steps are as follows:

[0056] Step 1 Preparation of Yb2Si2O7 powder

[0057] Yb(NO3)3·6H2O was dissolved in deionized water to obtain solution A; tetraethyl orthosilicate was dissolved in ethanol and stirred for 12 h to obtain solution B; solution A and solution B were stirred and mixed at room temperature to obtain transparent gel C; gel C was first dried at 80°C for 24 h, then dried at 110°C for 12 h, and finally heat treated at 1100°C for 2 h to obtain powder D; powder D was ball milled with a planetary ball mill for 30 min, and this process was repeated 10 times with a time interval of 15 min between two adjacent times, and Yb2Si2O7 powder was obtained after drying.

[0058] Wherein, the molar ratio of Yb(NO3)3·6H2O, ethyl orthosilicate, ethanol and deionized water is 1:1.2:4:4.

[0059] Step 2 Preparation of BaSrAlSiO powder

[0060] BaCO3, Al(NO3)3·9H2O and Sr(NO3)2 were dissolved in citric acid to obtain solution E; ethyl orthosilicate was dissolved in ethanol and stirred for 12 h to obtain solution F; solution E and solution F were mixed and stirred at room temperature to obtain transparent gel G; gel G was first dried at 80°C for 24 h and then dried at 110°C for 12 h to obtain powder H; powder H was ball milled with a planetary ball mill for 30 min, and this process was repeated 10 times with an interval of 15 min between two adjacent times to obtain BaSrAlSiO powder after drying.

[0061] Among them, the molar ratio of BaCO3, Al(NO3)3·9H2O, Sr(NO3)2, tetraethyl orthosilicate, ethanol and citric acid is 1:2:1:1.2:3:3.

[0062] Step 3 Preparation of TiO2nws powder

[0063] Tetrabutyl titanate was mixed with isopropanol and NaOH solution with a molar concentration of 0.08-0.12 mol / L in a volume ratio of 1:2:2 to obtain solution I, which was then stirred for 30 min and transferred to a 100 mL reactor for hydrothermal reaction at 180°C for 12 h. After natural cooling, the reaction precipitate was first washed with deionized water, then washed with HCl solution with a molar concentration of 0.1 mol / L to pH = 7, filtered, and the filter cake was dried at 80°C to obtain powder J. Powder J was calcined at 800°C in air for 2 h to obtain TiO2nws powder.

[0064] Step 4 Preparation of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics

[0065] Weigh 3 portions of 2.0 g Yb2Si2O7 powder and 0.2 g TiO2nws powder, mix them evenly with 0.2 g, 0.4 g, and 0.6 g BaSrAlSiO powder, respectively, and then press them into shapes (cold pressed into 35×15×4 mm2) at a pressure of 20 MPa. 3 After sintering in air at 1300°C for 2 h, Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics with different BaSrAlSiO contents were obtained.

[0066] Among them, the first generation of Yb2Si2O7-TiO2nws ceramics such as Figure 1 As shown in (a), it is in a porous state. Figure 1 (b) is the SEM image of the composite ceramic when 0.2 g BaSrAlSiO is added. It can be seen from the figure that the microstructure of the pressed ceramic is uniform, the grains are equiaxed, and the surface is smooth and dense. Figure 1 (c) is the SEM image of the composite ceramic when 0.4 g BaSrAlSiO is added. It can be seen that with the increase of BaSrAlSiO content, a thin film coating containing BaSrAlSiO and TiO2 gradually forms on the micro surface of the sample. Figure 1 (d) is the SEM image of the composite ceramic when 0.6g BaSrAlSiO is added. It can be seen that the surface area of ​​the polymerized BaSrAlSiO and TiO2 film increases. In addition, compared with the sample prepared with 0.2g BaSrAlSiO, the samples with 0.4g BaSrAlSiO and 0.6g BaSrAlSiO show a larger area of ​​thin film coating. It is well known that the microstructure of the coating, such as particle porosity and aggregation distribution, plays a vital role in the dielectric and microwave absorption properties of the ceramic coating, so in comparison, the sample with 0.6g BaSrAlSiO has better microwave absorption performance.

[0067] The XRD patterns of Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics with different BaSrAlSiO powder contents prepared in Example 1 are shown in Figure 2 As shown in the figure, it can be found that the characteristic peak of Yb2Si2O7 appears, and with the increase of BaSrAlSiO content, the peak intensity gradually increases.

[0068] Figure 3TEM image of the Yb2Si2O7-BaSrAlSiO / TiO2nws ceramic prepared in Example 1 with a BaSrAlSiO powder content of 0.6 g (i.e., the ratio of Yb2Si2O7, BaSrAlSiO and TiO2 is 10:3:1). As can be seen from (a), the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic is composed of particles of different sizes. Through high-resolution (b)-(d), it can be found that the lattice spacing of 0.32 nm corresponds to Yb2Si2O7, and the lattice spacing of 0.24 nm corresponds to TiO2.

[0069] from Figure 4 It can be seen that when the content of BaSrAlSiO powder is 0.2g, the minimum reflectance (RL min ) is -5dB; when the content of BaSrAlSiO powder is 0.4 g, RL min As the content of BaSrAlSiO powder increases to 0.6 g, RL min It can reach -35 dB, achieving 99.99% absorption of electromagnetic waves. In addition, it also has the largest EAB value among the three samples, which can reach 4.1 GHz. Therefore, it can be determined that the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic prepared by the present invention can be better used as an absorbing material in the field of microwave absorption, and has good absorbing performance and application prospects.

[0070] Example 2

[0071] A method for preparing Yb2Si2O7-BaSrAlSiO2 / TiO2nws composite ceramics, the specific steps are as follows:

[0072] Step 1 Preparation of Yb2Si2O7 powder

[0073] Yb(NO3)3·6H2O was dissolved in deionized water to obtain solution A; tetraethyl orthosilicate was dissolved in ethanol and stirred for 12 h to obtain solution B; solution A and solution B were stirred and mixed at room temperature to obtain transparent gel C; gel C was first dried at 90°C for 20 h, then dried at 130°C for 13 h, and finally heat treated at 1200°C for 2.5 h to obtain powder D; powder D was ball milled with a planetary ball mill for 20 min, and this process was repeated 15 times with a time interval of 10 min between two adjacent times to obtain Yb2Si2O7 powder after drying.

[0074] Wherein, the molar ratio of Yb(NO3)3·6H2O, ethyl orthosilicate, ethanol and deionized water is 1:1.2:4:4.

[0075] Step 2 Preparation of BaSrAlSiO powder

[0076] BaCO3, Al(NO3)3·9H2O and Sr(NO3)2 were dissolved in citric acid to obtain solution E; ethyl orthosilicate was dissolved in ethanol and stirred for 12 h to obtain solution F; solution E and solution F were mixed and stirred at room temperature to obtain transparent gel G; gel G was first dried at 90°C for 20 h and then dried at 130°C for 12 h to obtain powder H; powder H was ball milled with a planetary ball mill for 20 min, and this process was repeated 10 times with a time interval of 10 min between two adjacent times to obtain BaSrAlSiO powder after drying.

[0077] The molar ratio of BaCO3, Al(NO3)3·9H2O, Sr(NO3)2, tetraethyl orthosilicate, ethanol and citric acid is 1:2:1:1.2:3:3.

[0078] Step 3 Preparation of TiO2nws powder

[0079] Tetrabutyl titanate was mixed with isopropanol and NaOH solution with a volume ratio of 1:2:2 to obtain solution I. After stirring for 20 min, the mixture was transferred to a 100 mL reactor and subjected to hydrothermal reaction at 190 °C for 11 h. After natural cooling, the reaction precipitate was washed with deionized water, and then washed with HCl solution with a molar concentration of 0.05 mol / L to pH = 6.5. After filtering, the filter cake was dried at 90 °C to obtain powder J. Powder J was calcined at 700 °C in air for 2.5 h to obtain TiO2nws powder.

[0080] Step 4 Preparation of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics

[0081] Weigh 2.0 g of Yb2Si2O7 powder, 0.2 g of TiO2nws powder, and 0.2 g of BaSrAlSiO powder, mix them evenly, and then press them into a shape (cold pressed into a size of 35×15×4 mm) at a pressure of 25 MPa. 3 After being sintered in air at 1200°C for 2.5 h, Yb2Si2O7 / TiO2nws ceramics with different BaSrAlSiO contents were obtained.

[0082] Example 3

[0083] A method for preparing Yb2Si2O7-BaSrAlSiO2 / TiO2nws composite ceramics, the specific steps are as follows:

[0084] Step 1 Preparation of Yb2Si2O7 powder

[0085] Yb(NO3)3·6H2O was dissolved in deionized water to obtain solution A; tetraethyl orthosilicate was dissolved in ethanol and stirred for 12 hours to obtain solution B; solution A and solution B were stirred and mixed at room temperature to obtain transparent gel C; gel C was first dried at 70°C for 30 hours, then dried at 150°C for 11 hours, and finally heat treated at 1150°C for 3 hours to obtain powder D; powder D was ball milled with a planetary ball mill for 60 minutes, and this process was repeated 5 times with a time interval of 20 minutes between two adjacent times to obtain Yb2Si2O7 powder after drying.

[0086] Wherein, the molar ratio of Yb(NO3)3·6H2O, ethyl orthosilicate, ethanol and deionized water is 1:1.2:4:4.

[0087] Step 2 Preparation of BaSrAlSiO powder

[0088] BaCO3, Al(NO3)3·9H2O and Sr(NO3)2 were dissolved in citric acid to obtain solution E; tetraethyl orthosilicate was dissolved in ethanol and stirred for 12 h to obtain solution F; solution E and solution F were mixed and stirred at room temperature to obtain transparent gel G; gel G was first dried at 70°C for 30 h and then dried at 150°C for 11 h to obtain powder H; powder H was ball milled with a planetary ball mill for 50 min, and this process was repeated 7 times with a time interval of 20 min between two adjacent times to obtain BaSrAlSiO powder after drying.

[0089] Among them, the molar ratio of BaCO3, Al(NO3)3·9H2O, Sr(NO3)2, tetraethyl orthosilicate, ethanol and citric acid is 1:2:1:1.2:3:3.

[0090] Step 3 Preparation of TiO2nws powder

[0091] Tetrabutyl titanate was mixed with isopropanol and NaOH solution with a molar concentration of 0.08-0.12 mol / L in a volume ratio of 1:2:2 to obtain solution I. After stirring for 60 min, the mixture was transferred to a 100 mL reactor and subjected to a hydrothermal reaction at 170°C for 13 h. After natural cooling, the reaction precipitate was first washed with deionized water, and then washed with HCl solution with a molar concentration of 0.15 mol / L until the pH value was close to 7.5. After filtering, the filter cake was dried at 70°C to obtain powder J. Powder J was calcined at 900 °C in air for 2 h to obtain TiO2nws powder.

[0092] Step 4 Preparation of Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics

[0093] Weigh 2.0 g of Yb2Si2O7 powder, 0.2 g of TiO2nws powder and 0.6 g of BaSrAlSiO powder and mix them evenly. Then press them into a shape (cold pressed into a size of 35×15×4 mm) at a pressure of 15 MPa. 3 After sintering in air at 1500°C for 1.5 h, Yb2Si2O7-BaSrAlSiO / TiO2nws ceramics with different BaSrAlSiO contents were obtained.

[0094] In the above embodiments, the order of steps 1-3 can be swapped, and there is no obvious time sequence between them.

[0095] The present invention also conducted performance testing on the samples prepared in Example 2 and Example 3. The sample prepared in Example 3 had higher antioxidant properties and better wave absorbing ability, which further confirmed that the solution of the present invention can be used in harsh environments and has good environmental adaptability.

[0096] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.

Claims

1. A method for preparing Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics, characterized in that: Yb2Si2O7 powder, BaSrAlSiO powder and TiO2nws powder are uniformly mixed in a mass ratio of 10:1-3:1, and then cold pressed at a pressure of 15-25 MPa. After pressing and molding, they are sintered in an air atmosphere at a temperature of 1100-1500°C for 1.5-2.5 h to obtain Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramics.

2. The preparation method according to claim 1, characterized in that: The preparation method of the Yb2Si2O7 powder is as follows: Dissolve Yb(NO3)3·6H2O in deionized water to obtain solution A; Dissolve ethyl orthosilicate in ethanol and stir to obtain solution B; At room temperature, solution A and solution B are mixed and stirred to obtain a transparent gel C; After the gel C is dried, it is calcined to obtain powder D; wherein the drying process conditions are: first drying at 70-90°C for 20-30h, and then drying at 110-150°C for 11-13h; the calcination process conditions are: calcination temperature is 1100-1200°C, and calcination time is 2-3h; The powder D was ball-milled for 20-60 min. This process was repeated 5-15 times with a time interval of 10-20 min between two adjacent millings. Yb2Si2O7 powder was obtained after drying.

3. The preparation method according to claim 1, characterized in that: The preparation method of the BaSrAlSiO powder is as follows: BaCO3, Al(NO3)3·9H2O and Sr(NO3)2 were dissolved in citric acid to obtain solution E; Dissolve ethyl orthosilicate in ethanol and stir to obtain solution F; At room temperature, solution E and solution F were mixed and stirred to obtain a transparent gel G; After the gel G is dried, powder H is obtained; wherein the drying process conditions are: first drying at 70-90°C for 20-30 h, and then drying at 110-150°C for 11-13 h; The powder H was ball-milled for 20-60 min. The process was repeated 5-15 times with a time interval of 10-20 min between two adjacent millings. BaSrAlSiO powder was obtained after drying.

4. The preparation method according to claim 1, characterized in that: The preparation method of the TiO2nws powder is as follows: Tetrabutyl titanate, isopropanol and a NaOH solution with a molar concentration of 0.08-0.12 mol / L were mixed in a volume ratio of 1:2:2 to obtain a solution I, and the solution was stirred for 20-60 min and then transferred to a reactor for a hydrothermal reaction at 170-190° C. for 11-13 h; After natural cooling, the reaction precipitate was washed with deionized water, and then washed with a 0.05-0.15 mol / L HCl solution until the pH value was 6.5-7.5, and then filtered, and the filter cake was dried at 70-90 ° C to obtain powder J; The powder J was calcined at 700-900 °C in air for 1.5-2.5 h to obtain TiO2nws powder.

5. The preparation method according to claim 2, characterized in that: The molar ratio of Yb(NO3)3·6H2O, ethyl orthosilicate, ethanol and deionized water is 1:1.2:4:4; The drying process conditions of gel C were: first drying at 80°C for 24 h, then drying at 110°C for 12 h; the calcination process conditions were: heat treatment at 1100°C for 2 h; Powder D was ball-milled for 30 min using a planetary ball mill. This process was repeated 10 times with a time interval of 15 min between each milling.

6. The preparation method according to claim 3, characterized in that: The molar ratio of BaCO3, Al(NO3)3·9H2O, Sr(NO3)2, tetraethyl orthosilicate, ethanol and citric acid is 1:2:1:1.2:3:3; The process conditions for drying gel G were: first drying at 80°C for 24 h and then drying at 120°C for 12 h; The powder H was ball-milled for 30 min using a planetary ball mill. This process was repeated 10 times with a time interval of 15 min between each milling.

7. The preparation method according to claim 4, characterized in that: The molar concentration of the NaOH solution was 0.1 mol / L; solution I was stirred for 30 min, and the temperature of the hydrothermal reaction was 180 °C and the time was 12 h; The mixture was washed with 0.1 mol / L HCl solution until the pH value was 7, and then filtered. The filter cake was dried at 80° C. to obtain powder J. Powder J was calcined at 800 °C in air for 2 h to obtain TiO2nws powder.

8. A Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic, characterized in that: The product is prepared by the preparation method described in any one of claims 1 to 7.

9. Application of the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic as described in claim 8 in microwave absorption.

10. A wave absorbing material, characterized in that: Its effective component is the Yb2Si2O7-BaSrAlSiO / TiO2nws composite ceramic as described in claim 8.

Citation Information

Patent Citations

  • Method for preparing rod-like Yb2Si2O7 powder

    CN106064820A

  • Microwave composite ceramic BAl2SiO7-TiO2, and preparation method thereof

    CN106830909A